Ecological connectivity of genomic markers of antimicrobial resistance in Escherichia coli in Hong Kong - Xiaoqing Xu; Yunqi Lin; Yu Deng; Lei Liu; Dou Wang; Qinling Tang; Chunxiao Wang; Xi Chen; You Che; Ethan R. Wyrsch; Veronica M. Jarocki; Steven P. Djordjevic; et al. (Nature Communications)
Abstract Antibiotic-resistant Escherichia coli (E. coli) is a major contributor to the global burden of antimicrobial resistance (AMR). While the One Health concept emphasizes the connection of human, animal, and environmental health, genome-resolved and quantitatively integrated analyses of microbial exchange across ecological compartments remain limited. Here we show that E. coli populations from urban aquatic ecosystems in Hong Kong, representing human, animal, and environmental sources, exhibit close genetic relatedness. Using Nanopore long-read sequencing, we generated near-complete genomes for 1016 E. coli isolates collected over one year. These isolates encompassed all main phylogroups, 223 sequence types, 141 antibiotic resistance gene subtypes, and 2647 circular plasmids. 142 clonal strain-sharing events were detected between human-associated and environmental water samples. Additionally, 195 plasmids were shared across all three source-attributed sectors. Conjugation assays confirmed that several plasmids were functionally transmissible across ecological boundaries. To quantify these patterns, we established a genomic framework integrating sequence type similarity, genetic relatedness, and clonal sharing to assess ecological connectivity. Our results indicate that ecological connectivity may facilitate AMR dissemination, highlighting the importance of integrated strategies to monitor and manage resistance risks across sectors within the One Health framework.